2010
DOI: 10.1017/s0954579409990289
|View full text |Cite
|
Sign up to set email alerts
|

Attachment security and disorganization in maltreating and high-risk families: A series of meta-analyses

Abstract: The current meta-analytic study examined the differential impact of maltreatment and various socioeconomic risks on attachment security and disorganization. Fifty-five studies with 4,792 children were traced, yielding 59 samples with nonmaltreated high-risk children (n = 4,336) and 10 samples with maltreated children (n = 456). We tested whether proportions of secure versus insecure (avoidant, resistant, and disorganized) and organized versus disorganized attachments varied as a function of risks. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
414
4
19

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 696 publications
(475 citation statements)
references
References 112 publications
22
414
4
19
Order By: Relevance
“…A first is that a significant proportion of maltreated infants do not receive a classification of disorganized attachment with the maltreating caregiver in the Strange Situation. Although meta-analytic data show that maltreated infants are much more likely to receive a disorganized attachment classification than infants drawn from samples with few risk factors (Cyr, Euser, Bakermans-Kranenburg, & van IJzendoorn, 2010), such data also show that a large proportion of maltreated infants do not receive a disorganized classification (van IJzendoorn et al, 1999). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A first is that a significant proportion of maltreated infants do not receive a classification of disorganized attachment with the maltreating caregiver in the Strange Situation. Although meta-analytic data show that maltreated infants are much more likely to receive a disorganized attachment classification than infants drawn from samples with few risk factors (Cyr, Euser, Bakermans-Kranenburg, & van IJzendoorn, 2010), such data also show that a large proportion of maltreated infants do not receive a disorganized classification (van IJzendoorn et al, 1999). …”
Section: Introductionmentioning
confidence: 99%
“…Of particular relevance here for the issue of specificity is that for infants from families experiencing five or more socioeconomic risk factors, rates of disorganized attachment are also high, and similar in prevalence to samples of infants known to be maltreated (Cyr et al, 2010). Cyr and colleagues argue that such findings do not necessarily imply that these socioeconomic risk families with infants classified as disorganized all engage in maltreatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analytic study by Cyr, Euser, Bakermans-Kranenburg, and Van IJzendoorn (2010) identified seven socio-economic risk factors that significantly predict insecure and disorganized attachment. These are substance abuse, being part of a minority group, being an adolescent mother, low education, low income, single parenthood, and maltreatment.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, based on the meta-analytic links between accumulation of socio-economic risk and disorganized and insecure attachment (Cyr et al, 2010), a positive association was hypothesized between the sum of socio-economic risk factors and disorganized and insecure attachment. Thirdly, based on studies suggesting a protective effect of social support (Caron et al, 2005;Dolman et al, 2013) as well as based on qualitative reports of the importance of support figures in the lives of mothers with psychosis and/or HIV (Spies et al 2016), the hypothesis was tested that access to emotional support would compensate and buffer the risk of insecure and disorganized attachment.…”
Section: Introductionmentioning
confidence: 99%